Rupiah on Wheels: A Descriptive Study on the Investment Feasibility of Public Transportation Companies in Indonesia - La Ode Abdullah; Sugiharto Sugiharto; Dian Kusumaningrum; Niko Wahyu Dwi Hermawan (Brilliant International Journal Of Management And Tourism, 2025)
The rapid development of urban areas in Indonesia over the past two decades has significantly transformed mobility patterns and increased the importance of efficient public transportation systems. However, despite government initiatives to expand mass transport infrastructure, public transportation companies continue to face financial and structural challenges that affect their investment attractiveness. This study aims to assess the investment feasibility of public transportation companies listed on the Indonesia Stock Exchange (IDX) through a descriptive quantitative approach. Financial ratio analysis was employed, focusing on liquidity, solvency, profitability, and activity ratios, including Debt to Equity (DER), Times Interest Earned (TIER), Return on Assets (ROA), and Net Profit Margin (NPM). Secondary financial data were analyzed using descriptive statistics to evaluate the financial performance of selected companies between 2023 and 2024. The results reveal that most firms experienced notable improvements in solvency and profitability, with SDMU, NELY, and BIRD showing the highest increases in TIER at 69.73, 11.96, and 6.03 respectively, reflecting stronger operational efficiency and debt-servicing capacity. Conversely, JAYA and TAXI recorded declines of -0.80 and -18.72, indicating weaker financial stability. These findings suggest that the Indonesian public transportation sector demonstrates moderate but improving investment feasibility, offering attractive opportunities for medium- to long-term investors. The study concludes that companies such as SDMU, BIRD, NELY, and TMAS are financially more viable and potentially profitable investment choices, while firms with declining ratios should be approached cautiously. Ultimately, sustainable investment decisions in this sector should consider both financial and non-financial aspects, including governance, innovation, and social responsibility.